2020
DOI: 10.1111/joim.13101
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and renin‐angiotensin system inhibition: role of angiotensin converting enzyme 2 (ACE2) ‐ Is there any scientific evidence for controversy?

Abstract: Renin–angiotensin system (RAS) blockers are extensively used worldwide to treat many cardiovascular disorders, where they are effective in reducing both mortality and morbidity. These drugs are known to induce an increased expression of angiotensin‐converting enzyme 2 (ACE2). ACE2 acts as receptor for the novel SARS coronavirus‐2 (SARS‐CoV‐2) which raising the important issue of possible detrimental effects that RAS blockers could exert on the natural history and pathogenesis of the coronavirus disease‐19 (COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 120 publications
1
39
0
Order By: Relevance
“…Patients with pre-existing vascular risk factor burden such as hypertension and diabetes were likely to be treated with angiotensin-converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB). Both ACEI and ARB can upregulate ACE2, facilitating the SARS-CoV-2 entry into pneumocytes, and might cause exacerbation of the underlying disease [24]. However, available clinical evidence does not confirm an association between the use of ACEI or ARB and the poor outcomes of COVID-19 [7,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pre-existing vascular risk factor burden such as hypertension and diabetes were likely to be treated with angiotensin-converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB). Both ACEI and ARB can upregulate ACE2, facilitating the SARS-CoV-2 entry into pneumocytes, and might cause exacerbation of the underlying disease [24]. However, available clinical evidence does not confirm an association between the use of ACEI or ARB and the poor outcomes of COVID-19 [7,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…There are some contradictory results in such reports about the effect of such drugs on predisposition to COVID-19. 75 , 76 Many of the HPB suppressors affect ACE2 gene expression in a tissue-specific manner. 77 79 To the best of our knowledge, no experimental result has been published about the effect of ACE2-specific drugs on the affinity of ACE2 for S1 of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Spike (S) protein of SARS-CoV-2 binds with high a nity to human ACE2, and before SARS-CoV-2's entry into the cells [18][19][20], the S protein is subjected to a priming process via serine protease TMPRSS2 in order to permit the attachment of viral particles to ACE2 and thus on cell surface [21,22]. Therefore, SARS-CoV-2 can directly attack cardiac muscle cells through this pathway [23][24][25]. This entry mechanism is con rmed by the fact that TMPRSS2 inhibition or TMPRSS2-KO mice show both decreased, though not abolished, S protein priming, and reduced viral entry, spread, as well as, in ammatory chemokine and cytokine release [21].…”
Section: Discussionmentioning
confidence: 99%